(untitled) (Research, Society and Development, 2023)
The smile is the expression of happiness, and is directly related to the well-being and self-esteem of the individual. There are parameters that indicate the beauty of a smile, such as the position of the upper lip in relation to the gingival margin. When there is excessive gingival exposure, a clinical picture called gummy smile (GS) is characterized. For many, it is a non-aesthetic situation, and those who have this condition control or even hide their smile, as it affects their aesthetic and psychological state, leading to a decrease in their self-confidence. The etiology of the GS is multifactorial, so it is necessary to carry out a correct diagnosis to develop an individualized and adequate therapeutic plan, aiming beyond the multifactorial etiology of each case, the type of GS and the main muscles involved. Currently, the search for an aesthetic smile is becoming more and more common. A minimally invasive alternative that has been gaining strength in the dental market and serving as a substitute for surgical procedures is the use of botulinum toxin. The present work evaluates the characteristics of botulinum toxin type A (TXBA) and a SG, and associates them by analyzing the application of TXBA as an alternative treatment for muscle hyperfunction. Therefore, the objective of this work is, through a literature review, to evaluate the characteristics of TXBA and a SG, and to associate them by analyzing the application of TXBA as an alternative treatment for muscle hyperfunction.